On the misery of losing self-employment - Clemens Hetschko (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
German Socio-Economic Panel data is used to show that the decrease in life satisfaction caused by an increase in the probability of losing work is higher when self-employed than when paid employed. Further estimations reveal that becoming unemployed reduces self-employed workers' satisfaction considerably more than salaried workers' satisfaction. These results indicate that losing self-employment is an even more harmful life event than losing dependent employment. Monetary and non-monetary reasons seem to account for the difference between the two types of work. Moreover, it originates from the process of losing self-employment and the consequences of unemployment rather than from advantages of self-employment.
Keywords: I31; J24; J65; L26; 330; life satisfaction; self-employment; probability of losing work; Unemployment; SOEP